Mitigation Task Force for Farmer and Worker in Indonesia: A Collaborative Governance Approach in Tobacco Control (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
Tobacco control for public health improvement has been mandated as a part of the Indonesian National Medium-Term Development Plan (RPJMN) 2020 – 2024, as Indonesia currently sits among the countries with the highest smoking prevalence. On the other hand, Indonesia's position as one of the largest tobacco producers requires proper mitigation strategies for specific communities directly exposed to the tobacco industry. Hence, solid and adequate intra-sectoral collaboration strategies need to be identified. A formal intra-sectoral collaboration creates a win-win solution for both public health and economic sectors, as witnessed by other countries with appropriate government collaboration formulation. This study aims to identify a suitable collaborative governance model for providing mitigation strategies for tobacco farmers and tobacco industry workers. This research investigates the feasibility and environment scanning through a qualitative approach. The data collection was conducted through four series of semi-structured focused group discussions with key policymakers, complemented with secondary data analysis. The Task Force model is the most suitable mitigation initiative for tobacco farmers and cigarette industry workers. It is also more manageable in terms of regulation since it needs minimum regulatory requirements. The task force model also enables more substantial synergies between the central and local governments. However, strong coordination, between-sectoral sentiments, and the need for strong political will remain challenges for the task force implementation.